Bi4TaO8Cl (at) g-C3N4 composite nanomaterial as well as preparation method and application thereof

By constructing Bi4TaO8Cl@g-C3N4 composite nanomaterials, using the excellent optical response and layered structure of g-C3N4 to form a heterojunction with Bi4TaO8Cl, the problem of insufficient energy utilization efficiency and piezoelectric induction strength of Bi4TaO8Cl in the field of piezoelectric catalysis is solved, and the catalytic performance and the efficiency of H2O2 generation reaction are significantly improved.

CN119838625AActive Publication Date: 2025-04-18SHANGHAI INST OF TECH

Patent Information

Application Number
CN202510116100.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

There are shortcomings in the practical application of Bi4TaO8Cl in the field of piezoelectric catalysis, including the band gap width limiting energy utilization efficiency, the offset of the random aggregation of nanosheets and the spontaneous polarization effect, resulting in insufficient piezoelectric induction intensity, affecting catalytic performance.

Method used

By constructing Bi4TaO8Cl@g-C3N4 composite nanomaterials, a heterojunction with Bi4TaO8Cl is used to construct a Bi4TaO8Cl with the excellent optical response and layered structure of g-C3N4, and the band structure and charge separation efficiency are optimized.

Benefits of technology

The catalytic performance is significantly improved and the efficiency of H2O2 generation reaction is improved. The H2O2 yield of Bi4TaO8Cl@g-C3N4 composite material is as high as 493μmol/L, far exceeding the yield of a single Bi4TaO8Cl, proving the huge advantage of heterojunction structure in improving the piezoelectric catalytic performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005257854090000011
    Figure HDA0005257854090000011
  • Figure HDA0005257854090000012
    Figure HDA0005257854090000012
  • Figure HDA0005257854090000021
    Figure HDA0005257854090000021
Patent Text Reader

Abstract

The invention relates to a Bi4TaO8Cl (at) g-C3N4 composite nanomaterial as well as a preparation method and application thereof, and the preparation method comprises the following steps: respectively carrying out calcination pretreatment on BiOCl, Bi2O3 and Ta2O5, uniformly mixing the BiOCl, Bi2O3 and Ta2O5 subjected to calcination pretreatment, adding a molten salt aid, uniformly mixing, calcining, and washing the calcined product to obtain a Bi4TaO8Cl nanosheet; the preparation method comprises the following steps: dispersing g-C3N4 and a Bi4TaO8Cl nanosheet in water, and carrying out ultrasonic compounding, so as to obtain the Bi4TaO8Cl-coated g-C3N4 composite nano material. When the material is subjected to mechanical vibration to generate piezoelectric potential, electrons and holes can be effectively separated under the action of an electric field and migrate in different directions, so that the recombination rate of the electrons and the holes is remarkably reduced, more carriers participate in the reaction of catalyzing to generate H2O2, and the catalytic efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of piezoelectric catalysis technology, and in particular to a Bi4TaO8Cl@g-C3N4 composite nanomaterial and a preparation method and application thereof. Background Art

[0002] In the field of catalysis, the key to improving reaction efficiency lies in achieving effective separation and efficient transmission of photogenerated or piezoelectrically generated carriers, while suppressing the rapid recombination of electron-hole pairs as much as possible. This requires optimization through a variety of strategies, including precise regulation of the band structure, construction of heterojunctions to form a built-in electric field to enhance the ability of interfacial charge separation, increasing the exposure ratio of active sites on the surface of the material, and optimizing the application method of external fields (such as mechanical vibration or electric field). In recent years, piezoelectric catalysis technology has gradually become a research hotspot in the design of efficient catalysts because of its characteristics of generating piezoelectric potential to drive reactions through mechanical vibration without the need for external light sources. Piezoelectric potential can not only provide a long-range driving force to promote the separation of carriers, but also suppress carrier recombination through electrostatic screening effects and prolong its life, providing a more efficient energy utilization pathway for catalytic reactions. In addition, the charge accumulation and depletion effects caused by piezoelectric potential can optimize the surface energy band distribution of the material and further enhance the adsorption capacity of polar molecules or ions.

[0003] As a layered perovskite oxide material, Bi4TaO8Cl is an ideal candidate for studying piezoelectric catalysis due to its excellent piezoelectric properties and unique structural characteristics. 2+ Layer with (TaO4Cl) 2- The layers are arranged alternately to form a layered perovskite structure, which not only provides a natural charge migration channel, but also exhibits high spontaneous polarization and ferroelectric properties. In particular, the coherent off-center displacement of Bi4TaO8Cl makes its internal charge distribution more uniform, thereby enhancing the spontaneous polarization effect and piezoelectric response of the material. Under the conditions of mechanical vibration or external strain, this structural characteristic can further destroy the electrostatic shielding effect inside the material and significantly enhance the strength of the piezoelectric potential, thereby more efficiently driving charge separation and migration and promoting the catalytic reaction.

[0004] Although Bi4TaO8Cl has a large piezoelectric driving ability and strong redox ability in theory, its practical application in the field of piezoelectric catalysis still has obvious shortcomings. First, due to its band gap width of about 3.0eV, it has strong absorption only in the ultraviolet region, which limits its catalytic efficiency in a wider spectrum energy range. Secondly, the random directional distribution of its spontaneous polarization may offset each other after the nanosheets are aggregated, significantly reducing the piezoelectric induction intensity. In addition, although the conduction band position of Bi4TaO8Cl (-1.05eV, relative to NHE) is sufficient to drive some oxygen reduction reactions, its higher valence band position (1.85eV) limits the charge separation efficiency and affects the overall catalytic performance. Therefore, through reasonable design and optimization, such as constructing a heterojunction or introducing external strain, its catalytic performance can be further improved, so that it can play a greater potential in the field of piezoelectric catalysis.

[0005] Bi4TaO8Cl has been used as a ferroelectric material in the field of piezoelectric catalysis and has achieved some outstanding results. For example, in the field of piezoelectric catalytic water decomposition, Bi4TaO8Cl has been proposed for efficient seawater decomposition reaction. Without any catalyst or scavenger, its hydrogen production rate reaches 1.5mmol g -1 h -1 , and simultaneously generate the value-added chemical H2O2. Although the hydrogen production rate using seawater as the reaction medium is slightly lower, it is still better than the performance of most oxide catalysts and piezoelectric catalysts in photocatalytic H2 production. The study analyzed its reaction mechanism through a double-layer model, providing important theoretical support for future material optimization.

[0006] However, this system still has shortcomings: the band gap width of Bi4TaO8Cl (~3.0eV) limits its energy utilization efficiency, while the random aggregation of nanosheets and the offset of spontaneous polarization effects lead to insufficient piezoelectric induction intensity, which further limits the improvement of its catalytic performance. In addition, Bi4TaO8Cl has also been used for piezoelectric photocatalytic wastewater treatment. For example, single-crystal Bi4TaO8Cl nanosheets exhibit visible light response and significant piezoelectric behavior, producing 0.35% crystal deformation and band bending of more than 2.5eV under applied pressure. Using this material to treat five typical pollutants in the textile and pharmaceutical industries, the study found that it has excellent performance in piezoelectric catalysis, photocatalysis and the combined piezoelectric photocatalytic method, and achieved mineralization of all pollutants. This shows that combining piezoelectric effect and photocatalytic effect can produce a synergistic effect of more than 45%. However, this system still has problems with insufficient material stability and band structure matching. In particular, in the single Bi4TaO8Cl system, the recombination rate of electron-hole pairs is high, resulting in a decrease in efficiency under specific reaction conditions. Summary of the invention

[0007] The purpose of the present invention is to provide a Bi4TaO8Cl@g-C3N4 composite nanomaterial and a preparation method and application thereof in order to overcome at least one of the defects of the above-mentioned prior art.

[0008] The purpose of the present invention can be achieved through the following technical inventions:

[0009] One of the purposes of the present invention is to provide a method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial, comprising the following steps:

[0010] S1, BiOCl, Bi2O3 and Ta2O5 are calcined and pretreated respectively, and then the calcined BiOCl, Bi2O3 and Ta2O5 are mixed, and a molten salt additive is added and mixed uniformly, and then calcined, and the calcined product is washed to obtain Bi4TaO8Cl nanosheets;

[0011] Specifically, all components are thoroughly mixed together by mechanical grinding; after the mixture is evenly ground, it is transferred to an alumina crucible and calcined at high temperature; after the calcination, the crucible is naturally cooled to room temperature, and the product is repeatedly washed with a large amount of deionized water to completely remove the residual molten salt additives, and finally dried to obtain Bi4TaO8Cl nanosheets.

[0012] S2, dispersing g-C3N4 and Bi4TaO8Cl nanosheets in water, and ultrasonically compounding to obtain Bi4TaO8Cl@g-C3N4 composite nanomaterials;

[0013] Specifically, according to a certain mass ratio, appropriate amounts of Bi4TaO8Cl and g-C3N4 were weighed and added to deionized water, and composite treatment was performed using ultrasonic equipment. The appropriate ultrasonic frequency, power and time were adjusted to allow the two materials to be fully mixed and interact with each other to form a stable heterojunction structure. After the ultrasonic treatment was completed, the sample was dried to finally obtain a Bi4TaO8Cl@g-C3N4 composite material.

[0014] Further, the molar ratio of the BiOCl, the Bi2O3 and the Ta2O5 is (1-3): (1-2): 1. Preferably, the molar ratio of the BiOCl, the Bi2O3 and the Ta2O5 is 3:2:1.

[0015] Further, the molten salt additive is NaCl and KCl in a mass ratio of (1-3):(1-3). Preferably, the molten salt additive is NaCl and KCl in a mass ratio of 1:1.

[0016] Further, the calcination temperature is 700-800°C, the calcination time is 14-28h, and the heating rate is 3-5°C / min. Preferably, the calcination temperature is 700°C, the calcination time is 14h, and the heating rate is 5°C / min.

[0017] Furthermore, the preparation method of g-C3N4 is: using a nitrogen-containing organic compound as a precursor, and obtaining g-C3N4 through an intermolecular polycondensation reaction under high temperature conditions. In addition, the g-C3N4 can also be prepared by a template method, a pyrolysis nitridation method, and the like.

[0018] Furthermore, the nitrogen-containing organic compound is any one or more of melamine, urea and dicyandiamide.

[0019] Furthermore, the frequency of the ultrasound is 40±2kHz, the power is 500-600W, and the time is 20-60min.

[0020] Preferably, the ultrasonic power is 540W and the time is 30 minutes.

[0021] The second object of the present invention is to provide a Bi4TaO8Cl@g-C3N4 composite nanomaterial, which is prepared by the preparation method as described above. The composite nanomaterial is a heterojunction composite material formed by Bi4TaO8Cl nanosheets and g-C3N4, and the mass of the g-C3N4 is 1 to 4wt% of the heterojunction composite material, preferably 1wt%, 2wt%, 3wt% or 4wt%.

[0022] Furthermore, the particle size of the composite nanomaterial is 100-800 nm.

[0023] The third object of the present invention is to use the Bi4TaO8Cl@g-C3N4 composite nanomaterial as described above, which is used in piezoelectric catalysts.

[0024] Mechanism of action:

[0025] In the Bi4TaO8Cl@g-C3N4 heterojunction, the band gap of g-C3N4 is about 2.7eV, the conduction band position is -1.13eV, and the valence band position is 1.57eV, while the conduction band position of Bi4TaO8Cl is -1.05eV (relative to NHE) and the valence band position is 1.85eV. Compared with Bi4TaO8Cl, the conduction band and valence band positions of g-C3N4 are higher, and the work function is smaller. When the two semiconductor materials are in close contact, the electrons in g-C3N4 will spontaneously diffuse to Bi4TaO8Cl, and an electron depletion layer and an electron accumulation layer will be formed near the interface, making Bi4TaO8Cl negatively charged and g-C3N4 positively charged. Under the action of external mechanical stress, an internal piezoelectric field pointing from g-C3N4 to Bi4TaO8Cl will be generated at the interface of this heterojunction. This piezoelectric field effectively promotes the separation of charges and suppresses the recombination of charges.

[0026] In addition, when Bi4TaO8Cl and g-C3N4 come into contact, their Fermi levels are adjusted to the same level, which causes the Fermi level of Bi4TaO8Cl to move up, the Fermi level of g-C3N4 to move down, and a band bending to form at the interface. This band bending further enhances the driving force of the piezoelectric field on the directional migration of carriers. Although g-C3N4 itself does not usually have piezoelectric properties due to the symmetry of its two-dimensional layered structure, it can be induced to exhibit a certain elastic electric effect through modification. The specific method is to subject urea to a two-step high-temperature heat treatment to form the basic structure of g-C3N4, followed by ultrasonic exfoliation to enhance the polarization performance. Under the applied mechanical stress, the modified g-C3N4 may change its electron distribution and exhibit an elastic electric effect, thereby synergizing the piezoelectric effect of Bi4TaO8Cl and further improving the charge separation efficiency of the heterojunction. Under the combined action of the piezoelectric field and band bending, the polarization charge induced by mechanical stress accumulates near the interface. This polarization effect helps the directional separation and migration of piezoelectric charges by regulating the interface potential barrier of the heterojunction, thus avoiding the ineffective recombination of charges.

[0027] Therefore, the electrons accumulated in g-C3N4 and the holes accumulated in Bi4TaO8Cl will be retained and participate in the piezoelectric catalytic reaction. This mechanism significantly improves the catalytic performance and reflects the importance of the synergistic effect of the piezoelectric effect and interfacial charge separation. The layered structure and chemical stability of g-C3N4 can effectively reduce the random aggregation of Bi4TaO8Cl nanosheets, thereby avoiding the performance degradation caused by the offset of the polarization effect. This composite material optimizes the migration path of electrons and holes through band modulation, maximizing the interfacial charge separation efficiency.

[0028] In addition, the excellent optical response of g-C3N4 significantly expands the light absorption range of the composite material, enabling it to utilize light energy more efficiently and achieve the synergistic utilization of light and mechanical energy. The optimization of bandgap matching makes carrier migration more efficient, thereby ensuring the comprehensive performance improvement of the heterojunction in a multi-scale range. This performance improvement is attributed to the built-in electric field formed by the heterojunction, which not only promotes charge separation, but also enhances the charge transfer efficiency and material stability. By constructing the Bi4TaO8Cl@g-C3N4 heterojunction material, the limitations of Bi4TaO8Cl were successfully overcome. The optimized band modulation and charge transfer efficiency are significantly improved, enabling it to exhibit excellent performance in the H2O2 generation reaction.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] (1) The Bi4TaO8Cl@g-C3N4 composite nanomaterial provided by the present invention is constructed by heterojunction composite of Bi4TaO8Cl nanosheets and g-C3N4 to form a Bi4TaO8Cl@g-C3N4 composite nanomaterial. A built-in electric field is formed between the Bi4TaO8Cl nanosheets and g-C3N4. When the material is subjected to mechanical vibration to generate piezoelectric potential, electrons and holes can be effectively separated under the action of the electric field and migrate in different directions, thereby significantly reducing the recombination rate of electrons and holes, allowing more carriers to participate in the catalytic reaction of generating H2O2, and greatly improving the catalytic efficiency. Under the piezoelectric catalysis of one hour, the H2O2 production of Bi4TaO8Cl is 34μmol / L, that of g-C3N4 is 16μmol / L, and the production of the Bi4TaO8Cl@g-C3N4 composite material is as high as 493μmol / L, which is 15 times that of a single Bi4TaO8Cl.

[0031] (2) The preparation method of the Bi4TaO8Cl@g-C3N4 composite nanomaterial provided by the present invention is simple, environmentally friendly and low in cost.

[0032] (3) The Bi4TaO8Cl@g-C3N4 composite nanomaterial provided by the present invention has excellent catalytic efficiency when used as a piezoelectric catalyst to generate hydrogen peroxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 X-ray diffractometer patterns of the XRD patterns of g-C3N4, Bi4TaO8Cl, and CNBi-2 powders in the present invention;

[0034] Figure 2 The field emission scanning electron microscope morphology spectrum of the CNBi-2 powder in the present invention;

[0035] Figure 3This is the element mapping analysis diagram of CNBi-2 powder in the present invention;

[0036] Figure 4 This is a comparison diagram of the absorption spectra of g-C3N4, Bi4TaO8Cl, and CNBi-2 powders in the visible light range in the present invention;

[0037] Figure 5 This is a comparison chart of the piezoelectric catalytic performance of g-C3N4, Bi4TaO8Cl, and CNBi-2 materials in the present invention. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented on the premise of the technical invention of the present invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0039] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. If no specific conditions are specified, the conventional conditions or the conditions recommended by the manufacturer shall be followed. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0040] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0041] Bi4TaO8Cl has been used as a ferroelectric material in the field of piezoelectric catalysis and has achieved some outstanding results. For example, in the field of piezoelectric catalytic water decomposition, Bi4TaO8Cl has been proposed for efficient seawater decomposition reaction. Without any catalyst or scavenger, its hydrogen production rate reaches 1.5mmol g -1 h -1 , and simultaneously generate the value-added chemical H2O2. Although the hydrogen production rate using seawater as the reaction medium is slightly lower, it is still better than the performance of most oxide catalysts and piezoelectric catalysts in photocatalytic H2 production. The study analyzed its reaction mechanism through a double-layer model, providing important theoretical support for future material optimization.

[0042] However, this system still has shortcomings: the band gap width of Bi4TaO8Cl (~3.0eV) limits its energy utilization efficiency, while the random aggregation of nanosheets and the offset of spontaneous polarization effects lead to insufficient piezoelectric induction intensity, which further limits the improvement of its catalytic performance. In addition, Bi4TaO8Cl has also been used for piezoelectric photocatalytic wastewater treatment. For example, single-crystal Bi4TaO8Cl nanosheets exhibit visible light response and significant piezoelectric behavior, producing 0.35% crystal deformation and band bending of more than 2.5eV under applied pressure. Using this material to treat five typical pollutants in the textile and pharmaceutical industries, the study found that it has excellent performance in piezoelectric catalysis, photocatalysis and the combined piezoelectric photocatalytic method, and achieved mineralization of all pollutants. This shows that combining piezoelectric effect and photocatalytic effect can produce a synergistic effect of more than 45%. However, this system still has problems with insufficient material stability and band structure matching. In particular, in the single Bi4TaO8Cl system, the recombination rate of electron-hole pairs is high, resulting in a decrease in efficiency under specific reaction conditions.

[0043] To this end, the present invention provides a method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial, comprising the following steps:

[0044] S1, BiOCl, Bi2O3 and Ta2O5 are calcined and pretreated respectively, and then the calcined BiOCl, Bi2O3 and Ta2O5 are mixed, and a molten salt additive is added and mixed uniformly, and then calcined, and the calcined product is washed to obtain Bi4TaO8Cl nanosheets;

[0045] Specifically, all components are thoroughly mixed together by mechanical grinding; after the mixture is evenly ground, it is transferred to an alumina crucible and calcined at high temperature; after the calcination, the crucible is naturally cooled to room temperature, and the product is repeatedly washed with a large amount of deionized water to completely remove the residual molten salt additives, and finally dried to obtain Bi4TaO8Cl nanosheets.

[0046] S2, dispersing g-C3N4 and Bi4TaO8Cl nanosheets in water, and ultrasonically compounding to obtain Bi4TaO8Cl@g-C3N4 composite nanomaterials;

[0047] Specifically, according to a certain mass ratio, appropriate amounts of Bi4TaO8Cl and g-C3N4 were weighed and added to deionized water, and composite treatment was performed using ultrasonic equipment. The appropriate ultrasonic frequency, power and time were adjusted to allow the two materials to be fully mixed and interact with each other to form a stable heterojunction structure. After the ultrasonic treatment was completed, the sample was dried to finally obtain a Bi4TaO8Cl@g-C3N4 composite material.

[0048] In this embodiment, the molar ratio of the BiOCl, the Bi2O3 and the Ta2O5 is (1-3):(1-2):1;

[0049] Preferably, the molar ratio of the BiOCl, the Bi2O3 and the Ta2O5 is 3:2:1.

[0050] In this embodiment, the molten salt additive is NaCl and KCl in a mass ratio of (1-3):(1-3); preferably, the molten salt additive is NaCl and KCl in a mass ratio of 1:1.

[0051] In this embodiment, the calcination temperature is 700-800° C., the calcination time is 14-28 hours, and the heating rate is 3-5° C. / min.

[0052] Preferably, the calcination temperature is 700° C., the calcination time is 14 h, and the heating rate is 5° C. / min.

[0053] In this embodiment, the preparation method of g-C3N4 is: using a nitrogen-containing organic compound as a precursor, and obtaining g-C3N4 through an intermolecular condensation reaction under high temperature conditions.

[0054] Specifically, urea is placed in a crucible, and the temperature is gradually raised to a higher temperature and maintained for a period of time to allow the urea to undergo a preliminary thermal decomposition reaction to generate intermediate products; after the reaction is cooled to room temperature, the temperature is raised to an appropriate temperature again and maintained to further promote the decomposition and recombination of urea, ultimately forming the basic structure of g-C3N4; then, the obtained sample is placed in a tubular furnace and continues to be subjected to high-temperature heat treatment under an inert atmosphere; the prepared g-C3N4 needs to be subjected to ultrasonic exfoliation treatment before use, and is dispersed in deionized water, and the particles or flakes are fully dispersed through long-term ultrasonic action, and the suspension after ultrasonic treatment is dried to obtain a g-C3N4 sample.

[0055] In this embodiment, the nitrogen-containing organic compound is any one or more of melamine, urea, and dicyandiamide.

[0056] In this embodiment, the frequency of the ultrasound is 40±2kHz, the power is 500-600W, and the time is 20-60min. Preferably, the power is 540W, and the time is 30min.

[0057] This embodiment also provides a Bi4TaO8Cl@g-C3N4 composite nanomaterial, which is prepared by the above-mentioned preparation method, wherein the composite nanomaterial is a heterojunction composite material formed by Bi4TaO8Cl nanosheets and g-C3N4, and the mass of the g-C3N4 is 1-4wt% of the heterojunction composite material. The particle size of the composite nanomaterial is 100-800nm.

[0058] This embodiment also provides an application of the Bi4TaO8Cl@g-C3N4 composite nanomaterial as described above, and the material is applied to piezoelectric catalysts.

[0059] Mechanism of action:

[0060] In the Bi4TaO8Cl@g-C3N4 heterojunction, the band gap of g-C3N4 is about 2.7eV, the conduction band position is -1.13eV, and the valence band position is 1.57eV, while the conduction band position of Bi4TaO8Cl is -1.05eV (relative to NHE) and the valence band position is 1.85eV. Compared with Bi4TaO8Cl, the conduction band and valence band positions of g-C3N4 are higher, and the work function is smaller. When the two semiconductor materials are in close contact, the electrons in g-C3N4 will spontaneously diffuse to Bi4TaO8Cl, and an electron depletion layer and an electron accumulation layer will be formed near the interface, making Bi4TaO8Cl negatively charged and g-C3N4 positively charged. Under the action of external mechanical stress, an internal piezoelectric field pointing from g-C3N4 to Bi4TaO8Cl will be generated at the interface of this heterojunction. This piezoelectric field effectively promotes the separation of charges and suppresses the recombination of charges.

[0061] In addition, when Bi4TaO8Cl and g-C3N4 come into contact, their Fermi levels are adjusted to the same level, which causes the Fermi level of Bi4TaO8Cl to shift up, the Fermi level of g-C3N4 to shift down, and forms a band bending at the interface. This band bending further enhances the driving force of the piezoelectric field on the directional migration of carriers.

[0062] Although g-C3N4 itself does not usually have piezoelectric properties due to the symmetry of its two-dimensional layered structure, it can be induced to exhibit a certain elastic electric effect through modification. The specific method is to subject urea to a two-step high-temperature heat treatment to form the basic structure of g-C3N4, followed by ultrasonic exfoliation to enhance the polarization performance. Under external mechanical stress, the electron distribution of the modified g-C3N4 may change, exhibiting an elastic electric effect, thereby synergizing the piezoelectric effect of Bi4TaO8Cl and further improving the charge separation efficiency of the heterojunction. Under the combined action of the piezoelectric field and band bending, the polarization charge induced by mechanical stress accumulates near the interface. This polarization effect helps the directional separation and migration of piezoelectric charges by regulating the interface potential barrier of the heterojunction, avoiding the ineffective recombination of charges.

[0063] Therefore, the electrons accumulated in g-C3N4 and the holes accumulated in Bi4TaO8Cl will be retained and participate in the piezoelectric catalytic reaction. This mechanism significantly improves the catalytic performance and reflects the importance of the synergistic effect of the piezoelectric effect and interfacial charge separation. The layered structure and chemical stability of g-C3N4 can effectively reduce the random aggregation of Bi4TaO8Cl nanosheets, thereby avoiding the performance degradation caused by the offset of the polarization effect. This composite material optimizes the migration path of electrons and holes through band modulation, maximizing the interfacial charge separation efficiency.

[0064] In addition, the excellent optical response of g-C3N4 significantly expands the light absorption range of the composite material, enabling it to utilize light energy more efficiently and achieve the synergistic utilization of light and mechanical energy. The optimization of bandgap matching makes carrier migration more efficient, thus ensuring the comprehensive performance improvement of the heterojunction in a multi-scale range.

[0065] The present invention further verifies the superior performance of Bi4TaO8Cl@g-C3N4 heterojunction material. In the H2O2 generation reaction, the H2O2 production of single Bi4TaO8Cl and g-C3N4 is 34μmol / L and 16μmol / L, respectively, while the H2O2 production of Bi4TaO8Cl@g-C3N4 is as high as 493μmol / L, which is significantly increased by about 15 times. This performance improvement is attributed to the built-in electric field formed by the heterojunction, which not only promotes charge separation, but also enhances the charge transfer efficiency and material stability. By constructing the Bi4TaO8Cl@g-C3N4 heterojunction material, the limitations of Bi4TaO8Cl were successfully overcome. The optimized energy band modulation and charge transfer efficiency are significantly improved, enabling it to exhibit excellent performance in the H2O2 generation reaction.

[0066] Example 1

[0067] This example provides the preparation of Bi4TaO8Cl@g-C3N4 composite nanomaterials:

[0068] (1) 0.3141 g BiOCl, 0.6530 g Bi2O3 and 0.2210 g Ta2O5 were weighed respectively, and each raw material was placed in a muffle furnace for calcination pretreatment, and the temperature was slowly raised to 300 °C at a heating rate of 5 K / min and kept at this temperature for 5 hours;

[0069] After the calcination pretreatment, the dried BiOCl, Bi2O3 and Ta2O5 were mixed in a molar ratio of 3:2:1, and 2.9279 g NaCl and 3.7463 g KCl were added as molten salt additives, and the molar ratio of the molten salt additive was 1:1. All the components were placed together in an agate mortar and fully mixed by mechanical grinding;

[0070] The uniformly ground mixture was carefully transferred to an alumina crucible and placed in a muffle furnace for high-temperature calcination. The temperature was slowly raised to 700 °C at a heating rate of 5 K / min and kept at this temperature for 14 h.

[0071] After calcination, turn off the power of the muffle furnace and let the sample cool naturally to room temperature in the furnace. After the sample cools down, take out the crucible, transfer the sample to a beaker, add a large amount of deionized water and wash it several times. During each washing, stir the sample thoroughly to make the molten salt completely dissolved in the water, and then collect the precipitate by centrifugation. Repeat the washing process at least 5 times to ensure that all NaCl and KCl impurities are removed;

[0072] After washing, the product was dried in a vacuum oven at 60 °C for 5 h, and finally high-quality Bi4TaO8Cl nanosheets were obtained;

[0073] (2) Accurately weigh 10 g of urea, put it into a clean crucible, cover the crucible, put the crucible into a muffle furnace, set the temperature program so that the furnace is heated steadily to 550 ° C within 120 min, and keep it at this temperature for 2 h;

[0074] After the insulation is completed, turn off the power of the muffle furnace and let the sample cool naturally to room temperature in the furnace. After the sample is cooled, carefully remove the crucible cover and adjust the muffle furnace parameters again so that the furnace is heated to 500°C within 120 minutes and kept at this temperature for 2 hours.

[0075] After the reaction is completed, the sample is collected and transferred to a porcelain boat, and the porcelain boat is placed in a tube furnace. The tube furnace parameters are set so that it is heated to 500°C within 100 min and kept warm for 2 h under a nitrogen atmosphere. The nitrogen flow rate is controlled at 20-50 mL / min.

[0076] Finally, a g-C3N4 sample was obtained; 50 mg of the prepared g-C3N4 was taken and added to 100 mL of deionized water, and the solution was placed in an ultrasonic cleaner, the ultrasonic frequency was set to 40 kHz, the power was set to 540 W, and the ultrasonic treatment was performed for 10 h;

[0077] After the ultrasonic treatment, the solution was transferred to a vacuum drying oven and dried at 100 °C until all the water in the beaker evaporated, and the dried sample was collected for later use;

[0078] (3) According to the mass of g-C3N4 being 2wt% of the heterojunction composite material, 98mg Bi4TaO8Cl and 2mg g-C3N4 were accurately weighed, and they were placed in a clean beaker. An appropriate amount of deionized water was added to the beaker so that the sample was completely immersed in the water to form a uniform suspension. The beaker was placed in an ultrasonic cleaner, and the ultrasonic frequency was set to 40±2kHz and the power was set to 540W, and the ultrasonic treatment was performed for 30 minutes;

[0079] After the ultrasonic treatment, the solution was centrifuged to collect the precipitate, and the collected precipitate was transferred to a vacuum drying oven and dried at 60°C for 6 hours to obtain a Bi4TaO8Cl@g-C3N4 composite material.

[0080] Application Example 1

[0081] This application example uses the Bi4TaO8Cl@g-C3N4 composite material obtained in Example 1 to conduct a piezoelectric catalytic experiment, and the specific steps are as follows:

[0082] (1) Accurately weigh 50 mg of the prepared Bi4TaO8Cl@g-C3N4 composite material and disperse it in 100 mL of pure water to form a uniform dispersion.

[0083] (2) The above dispersion was transferred to a reaction bottle, and the reaction bottle was placed in an ultrasonic bath. The ultrasonic frequency was set to 40 kHz and the experiment was carried out.

[0084] During the ultrasonic vibration process, the temperature of the reaction system is precisely controlled at 15°C by the circulating water cooling system. The water flow rate of the circulating water cooling system should be controlled within an appropriate range, generally 100-200 mL / min, to ensure a good cooling effect.

[0085] (3) During the reaction, 3 ml of the reaction solution was taken out every 20 minutes using a syringe, filtered through a 0.22 μm organic filter, and the filtrate was collected. Samples were taken at three time points for subsequent analysis.

[0086] (4) For the detection of hydrogen peroxide, the filtered sample was mixed evenly with 1 mL of 0.4 M KI solution and 1 mL of 0.1 M potassium hydrogen phthalate solution.

[0087] Then, UV-visible spectrometer was used to measure KI / H 32 Mo7N6O 28 Combined absorbance at 351nm. Before measuring the absorbance, the UV-Vis spectrometer must be calibrated to ensure the accuracy of the measurement results.

[0088] According to the pre-drawn standard curve, the concentration of H2O2 in the sample was calculated by the absorbance value, thereby evaluating the piezoelectric catalytic performance of the composite material under different ultrasonic frequencies.

[0089] Figure 1 X-ray diffractometer patterns of g-C3N4, Bi4TaO8Cl, and CNBi-2 powders. X-ray diffraction analysis of Bi4TaO8Cl nanosheets, g-C3N4, and Bi4TaO8Cl@g-C3N4 composites was performed using a RigakuUltima IV diffractometer. During the measurement, Cu Kα radiation was used with a wavelength of The scanning range is set at 5-80°, and the step length is precisely controlled to 0.02°. The X-ray diffraction pattern of the Bi4TaO8Cl nanosheets obtained under this measurement condition can clearly present its crystal structure characteristics. The position, intensity and peak shape of each diffraction peak can be compared with the standard card to accurately judge the phase purity, crystallinity and crystal structure integrity of the prepared Bi4TaO8Cl nanosheets. For the X-ray diffraction pattern of g-C3N4, it can also reflect its unique crystal structure information, which helps to understand the structure formation during its preparation process. The X-ray diffraction pattern of the Bi4TaO8Cl@g-C3N4 composite material is the key basis for judging the composite effect of the two. In this spectrum, it can be observed that the characteristic diffraction peaks of Bi4TaO8Cl and g-C3N4 exist at the same time, and the position and intensity of the peaks may change to a certain extent compared with a single material. These changes can provide important clues for studying the interaction between the two components in the composite material, the change of the crystal structure and the formation of heterojunctions.

[0090] Figure 2 The field emission scanning electron microscope morphology of CNBi-2 powder. The morphology of Bi4TaO8Cl@g-C3N4 composite material was observed by field emission scanning electron microscope. The field emission scanning electron microscope spectrum ( Figure 2) can intuitively display the microstructural characteristics of the composite material. In the high-resolution image, it can be clearly distinguished that the Bi4TaO8Cl nanosheets present a sheet-like structure, with a relatively flat surface, relatively uniform thickness, and relatively regular edges. The g-C3N4 is in the form of a film, which tightly wraps the Bi4TaO8Cl nanosheets. This unique microstructure allows a large contact area between the two, which is conducive to the transfer and separation of charges at the interface, laying a good foundation for improving the catalytic performance of the material. Through further analysis of the image, detailed information such as the uniformity of coverage of the g-C3N4 film on the surface of the Bi4TaO8Cl nanosheet and the tightness of the junction between the two can also be observed, which are closely related to the performance of the composite material.

[0091] Figure 3 This is the element mapping analysis diagram of CNBi-2 powder. The element distribution mapping analysis of Bi4TaO8Cl@g-C3N4 composite material was carried out by energy dispersive X-ray spectroscopy (EDS) combined with field emission scanning electron microscopy (FESEM) to further explore the distribution characteristics of elements in the material. Figure 3 The EDS spectrum (a) of the composite material clearly shows the presence of the main elements Bi, Ta, Cl, C, O and N, indicating that the composition of the composite material is consistent with the design. From the Mapping diagram (bh), it can be observed that the Bi element (Figure c) is highly coincident with the Ta and Cl elements (Figure d, Figure g), showing the uniform distribution characteristics of the Bi4TaO8Cl nanosheets. The distribution of the C element (Figure e) and the N element (Figure h) corresponds to the presence of g-C3N4, which is uniformly covered on the surface of the Bi4TaO8Cl nanosheets in a thin film. The distribution characteristics of the O element (Figure f) show its uniform presence in the entire composite material, which is consistent with the oxide part of the Bi4TaO8Cl structure. Overall, the Mapping analysis further confirmed the good combination between the Bi4TaO8Cl nanosheets and the g-C3N4 film. The close contact between the two and the uniform element distribution provide ideal conditions for charge separation and transport at the interface, thereby improving the photocatalytic performance of the material. This result is highly consistent with the goal of composite material design and provides an experimental basis for further optimization of photoelectric performance.

[0092] Figure 4 This is a comparison of the absorption spectra of g-C3N4, Bi4TaO8Cl, and CNBi-2 powders in the visible light range. The absorption spectra of Bi4TaO8Cl nanosheets, g-C3N4, and Bi4TaO8Cl@g-C3N4 composite materials in the visible light range were measured using a UV-visible spectrometer, and the results were plotted as follows Figure 4. For Bi4TaO8Cl nanosheets, their absorption spectrum can reflect the light absorption characteristics of the material in the visible light region. By analyzing the position, intensity and absorption edge of the absorption peak, we can understand its absorption capacity for light of different wavelengths, and then infer its electronic structure and optical properties. The absorption spectrum of g-C3N4 reflects its unique absorption behavior in the visible light range. It usually has a strong absorption peak within a certain wavelength range, which is closely related to its own electronic transition and band structure. The absorption spectrum of Bi4TaO8Cl@g-C3N4 composite material is an important basis for studying the changes in optical properties after the two are combined. Compared with a single material, the absorption spectrum of the composite material may show redshift or blueshift, and the absorption intensity may also change. These changes may be due to the formation of the heterojunction structure, which leads to the redistribution of electronic states and the adjustment of the band structure, thereby affecting the material's absorption and utilization efficiency of light.

[0093] Figure 5 This is a comparison chart of the piezoelectric catalytic performance of g-C3N4, Bi4TaO8Cl, and CNBi-2 materials. Figure 5 , showing the performance comparison of Bi4TaO8Cl nanosheets, g-C3N4 and Bi4TaO8Cl@g-C3N4 composite materials prepared by the present invention in producing H2O2 per unit time. Under the same reaction conditions, the three materials were subjected to piezoelectric catalytic generation of H2O2 experiments, and the concentration of H2O2 at different reaction time points was measured. These data were plotted into a curve to form a performance effect diagram. It can be clearly seen from the figure that under the piezoelectric catalytic effect of one hour, the output of Bi4TaO8Cl was 34μmol / L, the output of g-C3N4 was 16μmol / L, and the output of Bi4TaO8Cl@g-C3N4 composite material was as high as 493μmol / L, which is 15 times the output of single Bi4TaO8Cl. This fully demonstrates the great advantage of heterojunction structure in improving the piezoelectric catalytic performance of materials. By analyzing the trend of the H2O2 generation rate of different materials at different reaction times, the catalytic activity and stability of the materials can be further understood, providing a strong reference for optimizing material performance and reaction conditions. For example, if the composite material maintains a high H2O2 generation rate for a long time, it means that it has good stability and sustained catalytic ability, which is conducive to large-scale production and long-term operation in practical applications.

[0094] In summary, the Bi4TaO8Cl@g-C3N4 composite material prepared by the present invention exhibits excellent catalytic activity in the formation reaction of hydrogen peroxide, and has high stability and long service life. By compounding Bi4TaO8Cl nanosheets with good photoelectric properties with g-C3N4, an efficient charge separation interface is formed, thereby significantly improving the catalytic efficiency of the material. The heterojunction structure between Bi4TaO8Cl and g-C3N4 promotes the migration of carriers in the material and enhances its performance in the catalytic reaction. This composite material has great potential in the field of catalysis, and is particularly suitable for reactions that require efficient charge separation and catalytic efficiency.

[0095] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical invention content of the present invention still belongs to the protection scope of the technical invention of the present invention.

Claims

1. A method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial, characterized in that: The steps include: S1, BiOCl, Bi2O3 and Ta2O5 are calcined and pretreated respectively, and then the calcined BiOCl, Bi2O3 and Ta2O5 are mixed, and a molten salt additive is added and mixed uniformly, and then calcined, and the calcined product is washed to obtain Bi4TaO8Cl nanosheets; S2. Disperse g-C3N4 and Bi4TaO8Cl nanosheets in water and perform ultrasonic compounding to obtain Bi4TaO8Cl@g-C3N4 composite nanomaterials.

2. The method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial according to claim 1, characterized in that: The molar ratio of the BiOCl, the Bi2O3 and the Ta2O5 is (1-3):(1-2):

1.

3. The method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial according to claim 1, characterized in that: The molten salt additive is NaCl and KCl in a mass ratio of (1-3):(1-3).

4. The method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial according to claim 1, characterized in that: The calcination temperature is 700-800° C., the calcination time is 14-28 hours, and the heating rate is 3-5° C. / min.

5. The method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial according to claim 1, characterized in that: The preparation method of g-C3N4 is: using a nitrogen-containing organic compound as a precursor, and obtaining g-C3N4 through an intermolecular condensation reaction under high temperature conditions.

6. The method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial according to claim 5, characterized in that: The nitrogen-containing organic compound is any one or more of melamine, urea and dicyandiamide.

7. The method for preparing a Bi4TaO8Cl@g-C3N4 composite nanomaterial according to claim 1, characterized in that: The frequency of the ultrasound is 40±2kHz, the power is 500-600W, and the time is 20-60min.

8. A Bi4TaO8Cl@g-C3N4 composite nanomaterial, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 7, the composite nanomaterial is a heterojunction composite material formed by Bi4TaO8Cl nanosheets and g-C3N4, and the mass of the g-C3N4 is 1 to 4wt% of the heterojunction composite material.

9. The Bi4TaO8Cl@g-C3N4 composite nanomaterial according to claim 8, characterized in that: The particle size of the composite nanomaterial is 100-800nm.

10. An application of the Bi4TaO8Cl@g-C3N4 composite nanomaterial as claimed in claim 8, characterized in that: The material is used in piezoelectric catalysts.

Citation Information

Patent Citations

  • Catalyst for selective catalytic reduction of nitric oxide and preparation method of catalyst

    CN106111183A

  • Bismuth chlorofluorotantalate and preparation method and application thereof

    CN108704652A

  • Preparation method of nitrogen and vanadium co-doped titanium dioxide / bismuth tantalate Z-type heterojunction photocatalyst and application thereof

    CN109289887A

  • Preparation graphite-like phase carbonitride / cadmium organic coordination polymer nanocomposite material and application of

    CN109289925A

  • Preparation method and application of g-C3N4 / BaTiO3 composite material

    CN113368881A

Cited By

  • Carbon-coated bismuth-tantalum oxide heterojunction catalyst as well as preparation method and application thereof

    CN120771856A

  • A carbon-coated bismuth-tantalum oxide heterojunction catalyst, a preparation method and application thereof

    CN120771856B